2013
DOI: 10.1021/am4002277
|View full text |Cite
|
Sign up to set email alerts
|

Aminated Poly(glycidyl methacrylate)s for Constructing Efficient Gene Carriers

Abstract: Aminated poly(glycidyl methacrylate) (PGMA) vectors could efficiently mediate gene delivery. Recently, we reported that ethanolamine (EA)-functionalized PGMA could provide high transfection efficiency, while exhibiting very low toxicity. Herein, different amine species, including 1-amino-2-propanol (AP1), 3-amino-2-propanol (AP2), EA, and N,N,-dimethylethylenediamine (DED), and its quaternized DED, were proposed to aminate PGMA. The DNA condensation abilities, pH buffering capacities, cytotoxicities, and gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 20 publications
1
31
0
Order By: Relevance
“…We selected GMA as the comonomer to tether the PSTG copolymers onto the surface of the PVC films. The epoxy groups of GMA possess high reactivities toward amino groups . In this study, the obtained PSTG polymers had both epoxy groups distributed randomly along the backbone and were grafted onto the amino‐functionalized PVC surface simply through the soaking of the films in PSTG solutions at 60 °C for 2 h. The grafting density of the PSTG copolymers (micrograms per square centimeter) as a function of the copolymer concentration was assessed through measurement of the weight increase of the films per unit surface area.…”
Section: Resultssupporting
confidence: 63%
“…We selected GMA as the comonomer to tether the PSTG copolymers onto the surface of the PVC films. The epoxy groups of GMA possess high reactivities toward amino groups . In this study, the obtained PSTG polymers had both epoxy groups distributed randomly along the backbone and were grafted onto the amino‐functionalized PVC surface simply through the soaking of the films in PSTG solutions at 60 °C for 2 h. The grafting density of the PSTG copolymers (micrograms per square centimeter) as a function of the copolymer concentration was assessed through measurement of the weight increase of the films per unit surface area.…”
Section: Resultssupporting
confidence: 63%
“…[63][64][65][66][67] In some cases, the tertiary amines were further quaternised through the use of an alkyl halide to give access to side-chain cationic polymers. 68,69 In most cases so far, atom transfer radical polymerization (ATRP) was used for the preparation of the PGMA scaffold. Haddleton and co-workers showed that synthesis by a cobaltcatalysed chain transfer polymerisation could lead to the polymer chains displaying a methacrylate chain-end.…”
Section: Functionalisation With Aminesmentioning
confidence: 99%
“…For example: various cationic PGMAs have been obtained as carriers for anionic biomolecules, especially plasmid DNA (pDNA); fluorescent PGMAs have been fabricated by modifying with conventional chromophores (e.g., pyrene) or aggregation induced emission chromophores (e.g., tetraphenylethylene); stimuli‐responsive or targeting groups (folate, azobenzene, ferrocene, cyclodextrins, disulfide bond, etc.) have also been introduced for targeted and controlled delivery . Benefiting from the advances of polymer science and the diversified functionality of PGMAs, a series of PGMAs‐based nanoassemblies, such as nanoparticles, micelles (spherical, cylindric, wormlike, etc.…”
Section: Introductionmentioning
confidence: 99%